Building on marginal and derelict land proceedings of a conference organized by the Institution of Civil Engineers and held in Glasgow on 7-9 May 1986. (Thomas Telford, 1987)
Building on marginal and derelict land is the focus of these papers. They discuss hydraulic fills, colliery discard lagoons, land affected by old mine workings and opencast mining, landfill sites of industrial mining, chemical and domestic waste, derelict sites of former industries, and conclude with technical notes.